RESEARCH OF RELATIONSHIPS BETWEEN IMPLICIT AND EXPLICIT HEALTHY OR UNHEALTHY FOOD RELATED COGNITIONS - Plotka, Irina; Blumenau, Nina; Igonin, Dmitry; Bolshakova, Aleksandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The research aim is to study the relationships between implicit and explicit healthy or unhealthy food related cognitions. Research questions: (1) Is there a relationship between the results of measurements of healthy or unhealthy food related cognitions by implicit and self-assessment procedures? (2) How are healthy or unhealthy food related implicit and explicit cognitions and somatic properties (weight, height, body mass index (BMI), age, sex) related? (3) What common factors underlie the relationship between implicit and explicit healthy or unhealthy food related cognitions and somatic properties? (4) What contribution to food related implicit cognitions is made by explicit attitudes (preference of healthy or unhealthy food, the recentness of consumption, awareness of healthy or unhealthy food, sensations of taste) and somatic properties? (5) What contribution to each food related explicit cognition is made by food related implicit cognitions, the other food related explicit cognitions and somatic properties? Method. Participants – 83 students, aged 19-35, M = 25.75, SD = 4.63 years. Measurements: the specially designed IAT and corresponding self-assessment procedures. Results. There is a relationship between the results of implicit and explicit measurements. The main contribution to implicit preference for food is made by the weight, sex and explicit preference, based on recentness of its consumption.